The Violence of Othering and (non-)Indigenous Revival: Aammton Alias’ The Last Bastion of Ingei: Imminent as Postcolonial Speculative Fiction of Brunei Darussalam - Ho, Hannah Ming Yit (SARE: Southeast Asian Review of English, 2020)
This paper examines an Anglophone Bruneian novel, The Last Bastion of Ingei (2016), by Aammton Alias, as postcolonial speculative fiction. Employing the double lines of enquiry provided by the Orientalist colonial gaze and ideology of progress, I discuss symbolic and materialist aspects of the violent processes of othering experienced within the Bruneian nation. The novel delineates the way that a colonial mindset undermines indigenous and minority identities. I contend that the hybridity of human-hantu relations functions as a strategy of resistance by collapsing demarcated boundaries between self and alien other. A further revival of the cultures of indigenous Malays, non-indigenous Ibans, and Penans within Brunei exhibits the extent to which the novel’s project of decolonization is promoted. Furthermore, a dystopian world of conflict is rejected in an ultimate desire for utopian peace and happiness as the novel calls for a suturing of social and racial divisions. To this end, a unified nation is yearned for via speculative scenes of reconciled relations of its family members. Hence, I argue that this novel offers a valuable critique of the conditions of postcolonial identity through contested powers, spaces and voices through its speculative narrative plot.